2012
DOI: 10.1002/app.38873
|View full text |Cite
|
Sign up to set email alerts
|

Role of poly(lactic acid) in the phase transition of poly(vinylidene fluoride) under uniaxial stretching

Abstract: The effect of poly (lactic acid) (PLA) on the crystalline phase transition of poly (vinylidene fluoride) (PVDF) from a-to b-phase under uniaxial stretching for immiscible PVDF/ PLA blends was investigated. The typical sea-island structure in the blends was found to facilitate the necking of PVDF and the transition from a-to b-phase due to the local stress distribution during stretching. The crystalline phase transition of PVDF in the blends is temperature-dependent and is affected by the content of PLA. The hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 50 publications
(82 reference statements)
1
24
0
Order By: Relevance
“…The change in viscoelastic properties in the PVDF/PA6 blends is much outstanding, as compared to other immiscible PVDF blends with coarse phase morphology. For instance, in a study regarding PVDF blends with polylactide (PLA), micron PLA droplets only have a slight effect on the viscoelastic properties of the blends …”
Section: Resultsmentioning
confidence: 99%
“…The change in viscoelastic properties in the PVDF/PA6 blends is much outstanding, as compared to other immiscible PVDF blends with coarse phase morphology. For instance, in a study regarding PVDF blends with polylactide (PLA), micron PLA droplets only have a slight effect on the viscoelastic properties of the blends …”
Section: Resultsmentioning
confidence: 99%
“…The β/α ratio at 160°C stays around a quite low level in a large strain range as discussed in Figure A, suggesting that the β‐crystal is not directly formed from the recrystallization. According to literatures which pointed that the amount of β‐structure must be increased at the expense of the α‐phase, the formation of β‐phase at 160°C could be confirmed as a “recrystallization (α‐crystal) ‐β‐phase transformation.” Deformation of semicrystalline polymers under stretching leads to the orientation of chains and even the breakage of crystals . The α‐crystal lamellae induced by recrystallization from the melting of lamellar fragments is chain extended fibrillar crystals which are imperfect.…”
Section: Resultsmentioning
confidence: 99%
“…β‐crystal can be obtained by different techniques, among which the mechanical stretching of α‐crystal is the most important one . Numerous publications reported characterization and understanding of the mechanically induced structure‐transformation . Necking, defect, and heterogeneous stress are considered to play important roles in the structure transformation.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that blend displays a bi‐continuous structure. [ 37 ] The amphiphilic JNS is preferentially located at the interface. Thanks to the irregular feature, the JNS becomes jamming at a low threshold ( Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…In the present case, the PVDF/PLLA blend at 60/40 (wt/wt) with a bi‐continuous structure was selected as the model. [ 37 ] After selectively etching PLLA with chloroform, the sample experiences a dramatic shrinkage to ≈100 µm from the original thickness of ≈300 µm (Figure S3a, Supporting Information). At the skin layers, the porous structure is less connected and easily disintegrated (Figure S3b, Supporting Information).…”
Section: Methodsmentioning
confidence: 99%